Analisis Finansial Penggemukan Sapi Potong (Suatu Kasus Penggemukan Sapi Potong Pada PT Sawarga Mulya Sadaya) - Dwidjono Hadi Darwanto; Is Zunaini Nursinah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2005)
The objective of this research are measure the rate of profit and firtacial feasibility of feed letters business. Descriptive methode was applied in this research, whlie data on input production in in analysis of feedlotters. Result of indicates that in one year per tail of call is able to achive at rate at about to Rp 317,155.00 and gross profit marjin equal to 0,0892, profit marjin is effort equal to 0.0599 and also nett profit matjin equal to 0.0539. Hereinafter the feedlotters business developed at the rate of interst abaot rerenct 20 at eight period wich positif NPV equal to Rp 1,823,169,910.00 and payback period ofinvestment one yearfive mont, JRR ofequal to 31.90%.